2011
DOI: 10.1016/j.cgh.2011.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Variable Reliability of Endoscopic Findings With White-Light and Narrow-Band Imaging for Patients With Suspected Eosinophilic Esophagitis

Abstract: Background & Aims Endoscopic findings have been used to support a diagnosis of eosinophilic esophagitis (EoE) and to assess response to therapy, but their reliability is unknown. The aim of the study was to assess inter- and intra-observer reliability of endoscopic findings with white-light endoscopy and to assess changes in inter-observer reliability when narrow band imaging (NBI) was added to white light. Methods We collected data from 35 academic and 42 community adult gastroenterologists using 2 self-adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
71
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 19 publications
8
71
2
2
Order By: Relevance
“…This study shows that endoscopic findings alone are not enough to confirm the diagnosis of EsEo, since seventeen patients exhibited some endoscopic alteration, although histology demonstrated less than five EOS/HPF. This situation is similar to other published studies where authors state that endoscopic findings are not reliable to define the diagnosis and treatment [42,43].…”
Section: Discussionsupporting
confidence: 76%
“…This study shows that endoscopic findings alone are not enough to confirm the diagnosis of EsEo, since seventeen patients exhibited some endoscopic alteration, although histology demonstrated less than five EOS/HPF. This situation is similar to other published studies where authors state that endoscopic findings are not reliable to define the diagnosis and treatment [42,43].…”
Section: Discussionsupporting
confidence: 76%
“…20 This result is consistent with the blue shift that has been observed in other studies, as well. 24 In order to address the focal and patchy nature of this disease, miniature two-photon imaging instruments [25][26][27] that are endoscope-compatible are being developed to collect MPM images in vivo. Conventional endoscopy alone has been found to be inadequate to support either diagnosis or treatment of EoE.…”
Section: Discussionmentioning
confidence: 99%
“…According to a meta-analysis conducted by Kim et al consisting primarily of retrospective studies involving adult cohorts, the overall pooled prevalence of endoscopic findings in patients with EoE was 44% rings, 21% strictures, 9% narrow caliber esophagus, 48% linear furrows, 27% white exudates, and 41% decreased vascularity, with a wide variation in the prevalence of those endoscopic findings between each report. This variation can be ascribed to a lack of an established diagnostic system via endoscopy in EoE, as indicated by the unsatisfactory interobserver agreement for the endoscopic findings [92]. On the other hand, when only the prospective studies were examined in the meta-analysis, 93% of patients were found to have at least one endoscopic abnormality.…”
Section: Endoscopic Findingsmentioning
confidence: 99%